191 Prognostic value of amyloid beta (1–40) in patients with acute myocardial infarction. (8th December 2021) - Gagno, Giulia; Janjusevic, Milijana; Fluca, Alessandra Lucia; Beltrami, Antonio Paolo; Sinagra, Gianfranco; Aleksova, Aneta
Abstract: Aims: Patients who have survived acute myocardial infarction (AMI) are at higher risk of developing several cardiovascular complications during follow-up and, unfortunately, appropriate risk stratification remains a major challenge. Amyloid-β 1–40 [Aβ (1–40)] has already emerged as a prognostic biomarker of cardiovascular mortality among patients with stable coronary heart disease due to its pathophysiological vascular inflammation properties. Methods and results: The relationship between plasma Aβ (1–40) concentrations and follow-up outcome was examined in a large prospective cohort of patients hospitalized for AMI (NSTEMI or STEMI). Total RNA was extracted from peripheral blood mononuclear cells (PBMC) to assess the expression levels of BACE1 and BACE1-AS. A total of 894 subjects (607 patients with STEMI and 287 patients with NSTEMI) were included in this study. The median plasma Aβ (1–40) concentration at admission was 96.59 (60.94–134.5) pg/ml. During the 83 month follow-up, 123 patients died and 78 patients developed HF. Higher Aβ (1–40) concentrations were able to predict an increased mortality risk during follow-up. In addition, in the cohort of patients older than 67 years, the plasma concentration of Aβ (1–40) strongly correlated with an unfavourable outcome, whereas in the cohort younger than 67 years did not. Conclusions: This is the largest single centre study investigating the role of plasma Aβ (1–40) concentration in predicting patient outcomes after AMI both STEMI and NSTEMI. Our data show a strong correlation between plasma Aβ (1–40) levels and mortality risk during follow-up. In addition, we confirmed a correlation between age and plasma Aβ (1–40) concentration, noting that Aβ (1–40) values are an incremental risk factor in relation to age for adverse outcomes.